Artificial emotional intelligence beyond East and West - Daniel White; Hirofumi Katsuno (Internet Policy Review, 2022)
Artificial emotional intelligence refers to technologies that perform, recognise, or record affective states. More than merely a technological function, however, it is also a social process whereby cultural assumptions about what emotions are and how they are made are translated into composites of code, software, and mechanical platforms that operationalise certain models of emotion over others. This essay illustrates how aspects of cultural difference are both incorporated and elided in projects that equip machines with emotional intelligence. It does so by comparing the field of affective computing, which emerged in the North-Atlantic in the 1990s, with kansei (affective) engineering, which developed in Japan in the 1980s. It then leverages this comparison to argue for more diverse applications of the culture concept in both the development and critique of systems with artificial emotional intelligence.
Keywords: 300; Artificial intelligence; Affective computing; Emotion; Engineering